Do naps benefit novel word learning? Developmental differences and white matter correlates. (January 2023) - van Rijn, E.; Gouws, A.; Walker, S.A.; Knowland, V.C.P.; Cairney, S.A.; Gaskell, M.G.; Henderson, L.M.
Abstract: Memory representations of newly learned words undergo changes during nocturnal sleep, as evidenced by improvements in explicit recall and lexical integration (i.e., after sleep, novel words compete with existing words during online word recognition). Some studies have revealed larger sleep-benefits in children relative to adults. However, whether daytime naps play a similar facilitatory role is unclear. We investigated the effect of a daytime nap (relative to wake) on explicit memory (recall/recognition) and lexical integration (lexical competition) of newly learned novel words in young adults and children aged 10–12 years, also exploring white matter correlates of the pre- and post-nap effects of word learning in the child group with diffusion weighted MRI. In both age groups, a nap maintained explicit memory of novel words and wake led to forgetting. However, there was an age group interaction when comparing change in recall over the nap: children showed a slight improvement whereas adults showed a slight decline. There was no evidence of lexical integration at any point. Although children spent proportionally more time in slow-wave sleep (SWS) than adults, neither SWS nor spindle parameters correlated with over-nap changes in word learning. For children, increased fractional anisotropy (FA) in the uncinate fasciculus and arcuate fasciculus were associated with the recognition of novel words immediately after learning, and FA in the right arcuate fasciculus was further associated with changes in recall of novel words over a nap, supporting the importance of these tracts in the word learning and consolidation process. These findings point to a protective role of naps in word learning (at least under the present conditions), and emphasize the need to better understand both the active and passive roles that sleep plays in supporting vocabulary consolidation over development.